Toxicological Assessment of Flavor Ingredients in E-Vapor Products - Sciuscio, Davide; Calvino-Martin, Florian; Kumar, Ashutosh; Langston, Timothy B.; Martin, Elyette; Marescotti, Diego; Mathis, Carole; Hoeng, Julia; Peitsch, Manuel C.; Smith, Donna C.; Gogova, Maria; Vanscheeuwijck, Patrick; et al. (Frontiers in Toxicology, 2022)
Many flavor ingredients are often used in potentially reduced-risk tobacco products (such as e-vapor products). Although most are “generally recognized as safe (GRAS)” when used in food, there is limited information available on their long-term health effects when delivered by inhalation. While obtaining route-of-exposure-specific toxicological data on flavor ingredients is critical to product evaluation, the large number of individual flavor ingredients available and their potential combinations render classical toxicological assessment approaches impractical, as they may require years of preclinical investigations and thousands of laboratory animals. Therefore, we propose a pragmatic approach in which flavor ingredients are initially assigned to groups of structurally related compounds (Flavor Groups), from which flavor group representatives (FGR) are then selected and tested individually and as a mixture in vitro and in vivo. The premise is that structurally related compounds would have comparable metabolic and biological activity and that the data generated using FGRs could support the toxicological assessment of other structurally related flavor ingredients of their respective Flavor Groups. This approach is explained in a step-wise manner and exemplified by a case study, along with its strengths, limitations as well as recommendations for further confirmatory testing. Once completed, this FGR approach could significantly reduce the time and resources required for filling the data gap in understanding the health risks of many flavor ingredients while also minimizing the need for laboratory animals.